PENEGAKAN HUKUM DALAM PENANGGULANGAN PEKERJA SEKS KOMERSIAL (PSK) DI KOTA SURAKARTA - RAHARJA, MUGI (Dinamika Hukum, 2015)
Activities of commercial sexual exploitation that occurs in Surakarta was very alarming and disturbing indeed that should be sought in order to suppress, restrict, reduce and abolished. Therefore, the government and the people of Surakarta has the responsibility to implement the guidance and protection of children and women, it is necessary for law enforcement action in the form of concrete programs and the elaboration of National Legislation and International on the protection of children and women. The purpose of this study is to assess the enforcement of the law as an effort to tackle prostitution in Surakarta and assess barriers in the process of enforcing the law against prostitution in Surakarta. The study was conducted in the city of Surakarta and Surakarta District Court. This type of research juridical sociological research that focused on reviewing the application of the rules or norms of positive law, and review the issues examined in terms of the science of law with a view as well as linking with the reality that is in the implementation that aimed to describe the activities / events in the natural daily practice. The nature of research is descriptive which describe or illustrate the process of law enforcement in an effort to cope against the practice of prostitution or commercial sex workers in the city of Surakarta. Source of data: primary and secondary. Data collection techniques with field studies and literature. Methods of data analysis using qualitative methods. Based on the results of the study indicate that law enforcement in an effort to cope against the prostitutes who were in Surakarta, by the enactment of Surakarta City Regulation No. 03 Year 2006 on Combating Commercial Sexual Exploitation, but does not have a significant impact on the activity of prostitution. Prostitution prevention efforts carried out, one of them with raids and the raids on places of prostitution and street prostitution by the authorities. Provision of guidance, moral education, mental and religious splash done to reduce the presence of prostitution activity growing more intense. The obstacles encountered in the process of enforcing the law against prostitution in Surakarta, among others: the complex problems (like poverty, government policies that are less sensitive to the problems of women and children, who do not support the news media about the commercial sexual exploitation of women, children), the challenges of society, and the barriers that come from perpetrators and families who are victims of commercial sexual exploitation itself. Keywords: Law Enforcement and Commercial Sex Workers.